The Effect of Providing Sugarcane Bagasse Compost (Saccharum Sp.) on the Growth of Tomato Plants (Solanum Lycopersicum) in Polybags - Eddiwal, Eddiwal; Laksono, Bangun Joko; Dewi, Marisa Rusdalena (Formosa Journal of Applied Sciences, 2024)
This research aims to make bagasse compost an alternative organic material to improve soil properties, making it ideal for the growth of tomato plants. The nutrient content in bagasse compost is N 1.18%, P 1.23%, K 1.90%, C 30.92%, and the C/N ratio is 26.2. The results of the descriptive analysis showed that after four weeks of watering and fertilizing with bagasse compost, the average height of the tomato plants was 45.5 cm, the length of the longest leaf was 5.7 cm, the width of the widest leaf was 3.3 cm, and the number of leaves was 80 pieces. on the plant, the root length was 23 cm, and the wet and dry weight of the plant was 38.35 and 22.81 grams respectively. Based on statistical data analysis, it can be seen that the growth of tomato plants is not affected by the use of bagasse compost. It can be seen that of the seven variables observed, only one variable, namely the widest leaf width, has an influence.